Open circuits the inner beauty of electronic components - Schlaepfer, Eric; Oskay, Windell H. (No Starch Press, 2023)
"Through full-color photographs, this book examines the "accidental beauty" of electronic components, or the aesthetic design of things consumers were never expected to see. Includes brief discussions of how these components work, how they were manufactured, and how they are used"--
Includes index
Keywords: Elektronisches Bauelement; Ästhetik; Elektrotechnik; Industriedesign